2011
DOI: 10.1021/ja203208t
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Carbene-Stabilized Disilicon

Abstract: Reaction of carbene-stabilized disilicon L:Si═Si:L (L: = :C{N(2,6-Pr(i)(2)C(6)H(3))CH}(2), 1) with BH(3)·THF results in facile cleavage of the silicon-silicon double bond and the formation of two quite different "push-pull" stabilized products with borane- and carbene-coordinated silylene moieties: 2, containing a parent silylene (:SiH(2)); and 3, containing a unique three-membered cyclosilylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 32 publications
4
66
0
3
Order By: Relevance
“…Indeed, conA C H T U N G T R E N N U N G sist-A C H T U N G T R E N N U N G ent with the high energy of the s bond, Robinson has found that reactions with species such as BH 3 results in cleavage of the SiÀSi bond in compound 3 Si. [30] Frenking has examined the properties of the as-yet-unknown NHC (14 E)-and phosphine (15 E)-stabilised E 1 complexes for E = Si-Pb. [13,31] The results revealed that in all cases two distinct lone pair orbitals are found about the E centres (Figure 7), and the L À E bonding is consistent with a "dative" (donor-acceptor) description.…”
Section: Group 14mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, conA C H T U N G T R E N N U N G sist-A C H T U N G T R E N N U N G ent with the high energy of the s bond, Robinson has found that reactions with species such as BH 3 results in cleavage of the SiÀSi bond in compound 3 Si. [30] Frenking has examined the properties of the as-yet-unknown NHC (14 E)-and phosphine (15 E)-stabilised E 1 complexes for E = Si-Pb. [13,31] The results revealed that in all cases two distinct lone pair orbitals are found about the E centres (Figure 7), and the L À E bonding is consistent with a "dative" (donor-acceptor) description.…”
Section: Group 14mentioning
confidence: 99%
“…[58] Our group performed a theoretical study investigating if the superior NHC donors could be used to stabilise Be 2 . Coordination by both two (30) and four (31) NHCs was considered. In all cases, from a thermodynamic perspective, a large stabilisation over free Be 2 was observed upon coordination.…”
Section: Recent Synthetic Accomplishmentsmentioning
confidence: 99%
“…It should be noted that BH 3 addition to 3 Si resulted in cleavage of the Si À Si bond. [25] [a] Units of kJ mol À1 . Thermochemical properties calculated at 298 K (unscaled B3LYP/TZVP vibration frequencies and thermal correction).…”
mentioning
confidence: 99%
“…[12] Verbindung 3 gehçrt zur Klasse der SchwerelementVinylidenanaloga ("schwere Vinylidene"), die wir als neuartige Bausteine in die Chemie der Gruppe 14 eingeführt haben. [13] Unabhängig voneinander berichteten Robinson et al [14] und Baceiredo et al [15] von basenkoordinierten Silacycloprop-1-ylidenen, in denen nur ein schweres Gruppe-…”
Section: Cyclopropeneunclassified